2017
DOI: 10.1016/j.niox.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Thiolate-based dinitrosyl iron complexes: Decomposition and detection and differentiation from S-nitrosothiols

Abstract: Dinitrosyl iron complexes (DNIC) spontaneously form in aqueous solutions of Fe(II), nitric oxide (NO), and various anions. They exist as an equilibrium between diamagnetic, dimeric (bi-DNIC) and paramagnetic, monomeric (mono-DNIC) forms. Thiolate groups (e.g., on glutathione or protein cysteine residues) are the most biologically relevant anions to coordinate to Fe(II). Low molecular weight DNIC have previously been suggested to be important mediators of NO biology in cells, and emerging literature supports th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 30 publications
7
36
0
Order By: Relevance
“…Others have reported the production of SNOs from cellular DNICs under hypoxic or anoxic conditions, thus minimizing the possibility of NO • oxidation reactions. However, these previous studies used HgCl 2 to selectively detect SNO concentrations, a method recently found to artifactually detect DNICs as SNOs (Keszler et al, 2017). Although recent closer examinations (Hickok et al, 2011(Hickok et al, , 2012 of this issue agree with our results that production of SNOs from DNICs is not a predominant mode of action of DNICs, if it occurs at all, we would submit that a validated method that selectively detects SNOs in the presence of DNICs is needed to address this question rigorously.…”
Section: Discussionsupporting
confidence: 62%
“…Others have reported the production of SNOs from cellular DNICs under hypoxic or anoxic conditions, thus minimizing the possibility of NO • oxidation reactions. However, these previous studies used HgCl 2 to selectively detect SNO concentrations, a method recently found to artifactually detect DNICs as SNOs (Keszler et al, 2017). Although recent closer examinations (Hickok et al, 2011(Hickok et al, , 2012 of this issue agree with our results that production of SNOs from DNICs is not a predominant mode of action of DNICs, if it occurs at all, we would submit that a validated method that selectively detects SNOs in the presence of DNICs is needed to address this question rigorously.…”
Section: Discussionsupporting
confidence: 62%
“…The sensitivity is in the nanomolar range. The method can be used with any type of gas or liquid sample, including cell lysates and tissue homogenates (68,69).…”
Section: Ozone-based Chemiluminescence Detection Of Nitric Oxide and mentioning
confidence: 99%
“…3). If buffer at neutral pH is used, only NO ⅐ as such will give a signal (69). One of the most popular reactants for chemiluminescent detection of NO ⅐ and its derivatives is an acidic triiodide solution (65).…”
Section: Ozone-based Chemiluminescence Detection Of Nitric Oxide and mentioning
confidence: 99%
See 2 more Smart Citations